Evaluation and effectiveness of a two-day Dementia training program for hospital staff working in an emergency department - Schneider, Julia; Miller, Jennifer; Teschauer, Winfried; Kruse, Andreas; Teichmann, Birgit (Journal of Alzheimer's disease, 2021)
Background: Entering the hospital via an Emergency Department (ED) is a pivotal moment in the life of People with Dementia (PwD) and often starts an avoidable downward spiral. Therefore, it is required to further educate ED staff to raise awareness of the needs of PwD. Although there are many studies about existing dementia training programs for the hospital setting, empirical evidence for the ED setting and cross-level training evaluations are lacking. Objective: The study aims to evaluate a two-day dementia training course for ED staff on the outcome levels of learning, individual performance, and organizational performance. Furthermore, the study examines whether the training fulfilled participants’ expectations. Methods: Mixed methods were used to assess data from head nurses, nursing, and administrative staff working in EDs. We conducted semi-structured interviews three weeks before (N=18) and eight months after (N=9) the training. Questionnaire data were assessed before the training, three months, and six months after the training (N=44). A qualitative content analysis was conducted to analyze qualitative data; quantitative data was described descriptively. Results: The intervention seems to be effective on both learning and individual performance levels. However, we did not observe any changes in the organizational performance. The training program met attendees’ expectations only partly. The working environment of EDs needs to be taken more into account. Conclusion: Hospital staffs’ expectations of a dementia training program depend on the work area in which they operate. Results support the implementation of intervention bundles to enable sustainable cross-level changes.
Gesehen am 17.12.2021